Analisis Keterkaitan Pengungkapan Risiko dalam Laporan Tahunan dengan Risiko Default Perusahaan - Muhammad Rizal; Yessica Amelia; Sri Utami Nurhasanah (Jurnal Visi Manajemen, 2025)
This study examines the relationship between risk disclosure in annual reports and a company's default risk through a qualitative literature review approach. Clear and transparent risk disclosure in annual reports can reduce market uncertainty and enhance the perception of the company's financial stability. Through the analysis of various previous studies, it was found that comprehensive risk disclosure can lower borrowing costs, improve the company's credibility, and reduce the potential for financial failure. However, external factors such as market conditions and company policies still play an important role in influencing default risk. This research provides insights that although risk disclosure is effective in managing default risk, other factors must be considered in the analysis of predicting corporate financial failure.